Evolution of the testis and spermatozoon in mice and rats (Subfamily Murinae) in the absence of sperm competition. (31st May 2018) - Peirce, E. J.; McLennan, H. J.; Tuke, J.; Leigh, C. M.; Breed, W. G.
Abstract: This study explores the potential effects of interspecific differences in breeding systems on testis organisation and sperm morphology of native murid rodents. It poses the question – what are the effects of depressed levels of intermale sperm competition, as indicated by small relative testes mass, on the morphology of testes and spermatozoa in murine rodents? Species from three separate murine tribes, those of the Hydromyini, Rattini and Arvicanthini, were investigated with low relative testes mass being used as a proxy for low, or non‐existent, levels of intermale sperm competition. The findings show that in only one of the tribes with low relative testes mass, that of the Hydromyini, was there a reduced testicular area occupied by seminiferous tubules, but in two of the tribes significantly smaller seminiferous tubule diameters were present. In all three tribes, most species with low relative testes mass had a highly derived sperm morphology that, unlike in species with large relative testes mass, had spermatozoa where the head lacked an apical hook, was highly variable in form, often had a very large acrosome overlying the apical region of the nucleus which suggests divergent processes of sperm–egg interaction at the time of fertilisation, and a significantly shorter tail. It is therefore hypothesised that, unlike in species with a large relative testes mass where high levels of intermale sperm competition maintain a streamlined sperm head with an apical hook to aid in zona penetration, in most species of murine rodents with low relative testes mass there is greater reliance on enzymatic digestion of the extracellular matrix around the egg, and especially that of the zona pellucida, to facilitate sperm penetration at the time of fertilisation. Abstract : This investigation determines the effects of depressed levels of intermale sperm competition, as shown by low relative testes mass, on testis and sperm morphology in three murine rodent tribes. In one, a reduced proportion of the testis is occupied by seminiferous tubules and, in two, smaller seminiferous tubule diameters. Notably in all three tribes there are highly divergent sperm morphologies with variable sperm heads that generally lack an apical occur hook, have a greatly reduced perforatorium but, in most, a much enlarged acrosome, as well as shorter tails. It is suggested that low, or non‐existant, levels of intermale sperm competition, as occurs in a monogamous mating system, result in relaxed selection for the production of highly streamlined sperm heads and long tails with the consequence that very variable and divergent sperm morphology evolves with, usually, greater acrosomal enzyme production and release to facilitate extracellular egg coat penetration at fertilisation.